Too big to be bad?: implications for theory and review of research on crimes, vices, and misdeeds in the casino culture of Macau - Zabielskis, Peter (Crime, law and social change, 2015)
This is a review article of research published in English and Chinese that focuses specifically on casino-related crime in Macau, the largest venue for legalized gambling in the world. It suggests rich possibilities for further research and theoretical thinking into the globally relevant, yet locally specific features of this Special Administrative Region of China. Following studies that identify residents’ perceptions of how their once-quiet enclave has changed under the impact of recent phenomenal growth in the casino industry, it includes discussion, not just of crimes, but of a range of undesirable roles, acts and outcomes currently supported and encouraged by Macau’s casino culture and its position in relation to mainland China. A structural tension is identified between gambling as the main source of government revenue and the need to control and enforce regulation of unsavory acts and their consequences, both legal and illegal. It presents a typology of socially defined roles and processes within this environment that permit such activities to continue even across, and sometimes because of, the borders of different governmental jurisdictions. It suggests that a theoretical approach that gives broad attention to social harm rather than specific, legally defined casino-related crimes may be the most appropriate way to study negative social impacts in this and other communities dominated by casino-related economies.